Women's dietary diversity in rural Bangladesh: Pathways through women's empowerment - Sinharoy, Sheela; Waid, Jillian; Wendt, Amanda; Gabrysch, Sabine (Maternal & child nutrition, 2018)
The relationship between women's empowerment and women's nutrition is understudied. We aimed to elucidate this relationship by quantifying possible pathways between empowerment and dietary diversity among women in rural Bangladesh. In 2015, we conducted a cross-sectional survey of 2,599 married women ages 15-40 (median: 25) living in 96 settlements of Habiganj District, Bangladesh, as a baseline for the Food and Agricultural Approaches to Reducing Malnutrition trial. We collected data on women's empowerment (highest completed grade of schooling and agency), dietary diversity, and demographic factors, including household wealth. We used exploratory factor analysis and confirmatory factor analysis on random split-half samples, followed by structural equation modelling, to test pathways from schooling, through domains of women's agency, to dietary diversity. Factor analysis revealed 3 latent domains of women's agency: social solidarity, decision-making, and voice with husband. In the adjusted mediation model, having any postprimary schooling was positively associated with voice with husband (β41 = .051, p = .010), which was positively associated with dietary diversity (β54 = .39, p = .002). Schooling also had a direct positive association with women's dietary diversity (β51 = .22, p < .001). Neither women's social solidarity nor decision-making mediated the relationship between schooling and dietary diversity. The link between schooling and dietary diversity was direct and indirect, through women's voice with husband but not through women's social solidarity or decision-making. In this population, women with postprimary schooling seem to be better able to negotiate improved diets for themselves.
First published: 01 August 2017
Gesehen am 17.10.2018